An Analysis of the Barabah Mandi Dance Style in Lima Puluh Kota Regency, West Sumatra Province - Anggini Syahril; Auliana Mukhti Maghfirah Mukhti; Zulfikar Rizki Ananda Rizki; Nurmalena Nurmalena; Sri Meiweni Basra Weni (Kirana Publisher (KNPub), 2026)
This study aims to examine the Barabah Mandi dance style found in Nagari Koto Tinggi, Lima Puluh Kota Regency, West Sumatra Province. The research method used is a qualitative research method with a descriptive analysis nature. Through this method, the researcher describes the data obtained in the field, then analyzes it according to the focus of the research problem. The theory used in this study is the theory of style by Alan Lomax and the theory of dance form by Sumandiyo Hadi. The Barabah Mandi dance is a new creative dance that grew and developed in Nagari Koto Tinggi, Lima Puluh Kota Regency, West Sumatra Province. This dance is inspired by a legend that tells the love story of a pair of lovers. The legend was then processed into a dance work that has a character or characteristic that can be seen in the dance form. The characteristics of the dance are influenced by the agrarian region and the dominant activities of the local community as farmers. So the style of the Barabah Mandi dance can be categorized as a darek style.